2019
DOI: 10.1177/0275074019840759
|View full text |Cite
|
Sign up to set email alerts
|

Public Professionals’ Engagement in Coproduction: The Impact of the Work Environment on Elderly Care Managers’ Perceptions on Collaboration With Client Councils

Abstract: In the context of public service delivery, public professionals nowadays intensively collaborate with citizens. The joint, sometimes mandatorily, efforts of citizens and professionals to provide public services have become known as “coproduction.” Although coproduction directly affects professionals’ work environment, professionals’ attitudes toward coproduction are hardly studied. This article explains variation in professionals’ engagement in coproduction from characteristics of their work environment, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…They are required to be outward-oriented, collaborative and creative to bring together a range of different stakeholders (e.g., Dickinson et al 2019;Rhodes 2016;Kruyen and van Genugten 2020;Vanleene et al 2018). This classic tension may thus be enhanced as a result of increasing expectations (Nederhand, van der Steen, and van Twist 2018;Nils and Vogel 2018;Mees et al 2019;Van Eijk and Steen 2019;Ianniello et al 2019). In connection to this, participatory processes may conflict with formal politics.…”
Section: Tensions In Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…They are required to be outward-oriented, collaborative and creative to bring together a range of different stakeholders (e.g., Dickinson et al 2019;Rhodes 2016;Kruyen and van Genugten 2020;Vanleene et al 2018). This classic tension may thus be enhanced as a result of increasing expectations (Nederhand, van der Steen, and van Twist 2018;Nils and Vogel 2018;Mees et al 2019;Van Eijk and Steen 2019;Ianniello et al 2019). In connection to this, participatory processes may conflict with formal politics.…”
Section: Tensions In Engagementmentioning
confidence: 99%
“…It is difficult to be facilitative and responsive if resources are scarce or if they have been allocated on the basis of pre-set goals and projects (Tuurnas 2015;Nederhand, van der Steen, and van Twist 2018;Aschhoff and Vogel 2019;Jaspers and Steen 2019;compare Hood 1991). In addition, a study by Van Eijk and Steen (2019) found that when organisations invest their resources in developing co-production and supporting structures, this also increases civil servants' willingness to engage in co-production projects.…”
Section: Tensions In Engagementmentioning
confidence: 99%
“…Despite the growing interest in engagement, we know relatively little about the actual, everyday work of civil servants (Rhodes, 2016;Van Dorp & t Hart, 2018), particularly when it comes to a participatory context (Fenwick, 2012;Van Eijk et al 2019). To capture civil servants' work in public engagement, we started from a practice-theoretical approach (Cook & Wagenaar, 2012;Sandberg & Tsoukas, 2011;Wagenaar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[24,25]) and patients' councils in health organisations collaborating in strategic decisions (e.g. [26,27]). Our preference for the term 'health provider' in the definition rather than 'professionals' allows us to go beyond the dyadic dimension (i.e.…”
Section: Introduction Background and Rationale Of The Studymentioning
confidence: 99%